Design Strategies and Knowledge in Object-Oriented Programming: Effects of Experience - Detienne, Francoise (Human-computer interaction, 1995)
Presents research findings from an empirical study of design strategies and knowledge used in object-oriented (OO) software design by programmers both experienced and not experienced with OO programming. Results indicated that levels of experience with OO programming affect the design process. (Author/JKP)